Determinan perilaku merokok elektrik mahasiswa - Sinaga, Talentha; Putri, Betania Narwastu; A'in, Nurul; Suwarni, Linda (Poltekkes Kemenkes Kupang, 2023)
Background: Based on research data in 2018 the number of active smokers in West Kalimantan was 15,135 people. Based on studies results, smoking behavior among college students is motivated by the emergence of prestige which affects their psychology. By smoking they feel that their identity is recognized in the group and think that they will not be rejected. Objective: This study aimed to determine the determinants of electric smoking behavior in students majoring in Public Health, Faculty of Health Sciences at the Muhammadiyah University of Pontianak. Method: The research design used a cross-sectional design with a total sample of 75 people using an accidental sampling technique. The data collected included gender, knowledge, perceptions, attitudes, affordability, exposure, and the influence of peers on e-smoking behavior. Data analysis used the chi-square test. Result: The results showed that there was a relationship between gender (PR = 1.7; 95% CI 1.161-2.519), attitudes towards e-cigarettes (PR = 0.; 95% CI = 0.462-0.954), and peer influence (PR = 0.6; 95) %CI 0.294-1.058) with electric smoking behavior (p-value <0.05). An anti-smoking campaign is needed, especially for e-cigarettes in educational institutions.